2018
DOI: 10.3389/fpsyg.2018.01011
|View full text |Cite
|
Sign up to set email alerts
|

Why the Conjunction Effect Is Rarely a Fallacy: How Learning Influences Uncertainty and the Conjunction Rule

Abstract: In this article we explore the relationship between learning and the conjunction fallacy. The interpretation of the conjunction effect as a fallacy assumes that all observers share the same knowledge, and that nobody has access to privileged information. Such situations are actually quite rare in everyday life. Building on an existing model of surprise, we prove formally that in the more typical scenarios, where observers are alert to the possibility of learning from event outcomes, the conjunction rule does n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
(105 reference statements)
0
1
0
Order By: Relevance
“…In this design, the relative amount of conjunction errors was significantly reduced (Hertwig and Gigerenzer, 1999;Fiedler, 1988) Gigerenzer argues that the conjunction error is reduced in a frequency format because individuals tend to represent probabilistic information in terms of frequencies (Gigerenzer, 1994). This is further supported by more recent work which demonstrated that when the Linda Problem is framed as a query search for a computer database, where the description is framed as a set of parameters (e.g., age = 31, college major = philosophy) conjunction errors are yet again reduced (Maguire et al, 2018). Table 4.1 summarizes key experimental manipulations and their relative incidence of conjunctive errors.…”
Section: The Linda Problemmentioning
confidence: 74%
“…In this design, the relative amount of conjunction errors was significantly reduced (Hertwig and Gigerenzer, 1999;Fiedler, 1988) Gigerenzer argues that the conjunction error is reduced in a frequency format because individuals tend to represent probabilistic information in terms of frequencies (Gigerenzer, 1994). This is further supported by more recent work which demonstrated that when the Linda Problem is framed as a query search for a computer database, where the description is framed as a set of parameters (e.g., age = 31, college major = philosophy) conjunction errors are yet again reduced (Maguire et al, 2018). Table 4.1 summarizes key experimental manipulations and their relative incidence of conjunctive errors.…”
Section: The Linda Problemmentioning
confidence: 74%